ENHANCING THE ROLE OF THE MALAY LANGUAGE (MBM) IN KNOWLEDGE AUGMENTATION, PRACTICAL APPLICATION, SKILL DEVELOPMENT, AND ATTITUDINAL GROWTH - Irma Wani Othman; Mohd Maziz al-Hadi Moharam; Hamida Ambo; Siti Maizurah Abd. Salam; Mohd Khairi Lebai Ahmad; Muhammad Safuan Yusoff (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The Malay language is a unifying factor among the diverse populace of Malaysia. It plays a pivotal role as a language of knowledge and communication in a multiracial country like Malaysia. Therefore, one of the prominent means by which a nation measures its proficiency in a language is through verbal communication using that language. This paper seeks to analyze the proficiency of the Malay language and its significance in daily life, particularly in the field of education. The study aims to identify the extent of Malay language proficiency within the community and to assess the competence of teachers and students in the practice of the Malay language. The discussion delves into findings that associate the Malay language as a language of knowledge. Consequently, this approach emphasizes the use of academic writing, especially through literature review, by gathering primary and secondary sources to substantiate facts related to actual events. Among the issues discussed are: 1. Promoting writing in the Malay language among academicians, 2. Upholding the Malay language within the secondary and primary education system, 3. The Malay language as a means of expressing knowledge in higher education institutions, and 4. Empowering the use of the Malay language among the community. The findings analyzed from this study indicate that the Malay Language Elevation Program (MBM) has not been executed as effectively as intended. This conclusion is drawn from clear data illustrating that the Malay language proficiency among students is not as satisfactory as desired, and the teaching skills of Malay language teachers are not at an optimal level. Furthermore, this is compounded by the failure of school administrators to establish an effective and efficient administrative atmosphere within their premises. This study proposes a reevaluation of the MBM program from the perspectives of school administration and the teaching methods employed by Malay language educators, to enhance the effectiveness and efficiency of the program implementation, thus ensuring the success of the students in this program in the future. Additionally, the process of realizing this program is also proof that all stakeholders within the country, including individuals, the community, and the government, play a significant role in its implementation. Schools, District Education Offices (PPD), State Education Departments (JPN), the Ministry of Education (KPM), and Higher Education Institutions (IPTA/S) can leverage the results of the study to take steps in increasing knowledge, use, skills, and attitudes regarding the effort to elevate the Malay language. The findings of this study can also serve as a valuable guide in the teaching and learning process at various levels of education in IPTA/S. Therefore, all parties must play their respective roles in realizing the effort to enhance knowledge for a broader segment of society, both in the present and the future.